The Influence of Education, Digital Literacy and Generation Z Performance on the Performance of Employees of the Ministry of Defence's Defence Establishment - Mustofa (Dinasti Publisher, 2025)
The unemployment rate in Indonesia is still quite high, and is the second highest among ASEAN countries. The unemployment rate in Indonesia for 2023 is 5.45% (Source: Bapenas). Although it decreased by 0.38% from the previous year, this figure is still considered high for the unemployment rate. One of the challenges for developing countries like Indonesia is how the country can employ generations, especially the younger generation. The best solution is to encourage the younger generation to do their own business or can be said to be entrepreneurs. In general, entrepreneurial activities are very helpful in reducing unemployment in Indonesia. So, what must be done is to teach entrepreneurial skills to students. Gen Z's skills in using technology encourage them to intend to become entrepreneurs. In this study, the research technique uses the Quantitative method. To support quantitative data, the author uses the help of qualitative methods in the form of interviews as supporting data for quantitative research results. The results of the study showed a joint influence between education, Digital Literacy and Generation Z Performance on employee performance at Baranahan Kemhan, directly affecting employee performance because it successfully combines the education they have, the technology used is very up-to-date, and the performance of Gen Z who have been familiar with technology since birth. The suggestions conveyed are the need for other educational support that can directly affect employee performance so that the achievement of tasks runs optimally so that employee performance can increase. It is necessary to provide positions that are in accordance with their abilities in the field of digital literacy so that the implementation of employee performance can run well. It is necessary to support technology and operational budgets to achieve optimal performance.